Nonlocal description of the nucleus-nucleus interaction - Chamon, L. C.; Pereira, D.; Hussein, M. S.; Cândido Ribeiro, M. A.; Galetti, D. [UNESP] (American Physical Society (APS), 1997)
A parameter-free nonlocal double-folding-inspired interaction is proposed for the nucleus-nucleus systems. Excellent reproductions of elastic scattering differential cross section data were obtained for several systems over a wide range of bombarding energies. Our results should be of value in the description of the scattering of other many-body systems.